2022
DOI: 10.1002/wnan.1780
|View full text |Cite
|
Sign up to set email alerts
|

Management of osteoarthritis: From drug molecules to nano/micromedicines

Abstract: With the change in lifestyle and aging of the population, osteoarthritis (OA) is emerging as a major medical burden globally. OA is a chronic inflammatory and degenerative disease initially manifesting with joint pain and eventually leading to permanent disability. To date, there are no drugs available for the definitive treatment of osteoarthritis and most therapies have been palliative in nature by alleviating symptoms rather than curing the disease. This coupled with the vague understanding of the early sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 144 publications
(204 reference statements)
0
10
0
1
Order By: Relevance
“…Compared with traditional antioxidants, the stability analysis indicated that the H 2 O 2 scavenging of Ta-NH 2 NPs was not in uenced by pH or temperature [32]. It is well known that the activities of ROS scavenging in traditional biological enzymes [33] were affected by the microenvironment of joint cavity, and this drawback might affect the therapeutic outcome due to the uctuation in physical and chemical properties of osteoarthritic joints.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with traditional antioxidants, the stability analysis indicated that the H 2 O 2 scavenging of Ta-NH 2 NPs was not in uenced by pH or temperature [32]. It is well known that the activities of ROS scavenging in traditional biological enzymes [33] were affected by the microenvironment of joint cavity, and this drawback might affect the therapeutic outcome due to the uctuation in physical and chemical properties of osteoarthritic joints.…”
Section: Resultsmentioning
confidence: 99%
“…Current therapeutic agents alter the OA pathogenesis by targeting the regulation of inflammatory processes or the expression of growth factors or aggrecans. 46 , 47 Articular cartilage, an avascular tissue that forms the articulating surface of all joints, possesses an ECM to support normal biomechanics and homeostatic properties of joint cartilage. Cartilage is unique due to its limited regenerative ability and avascular nature.…”
Section: Discussionmentioning
confidence: 99%
“…A number of drugs have been approved by the US Food and Drug Administration (FDA) to treat OA, such as Diclofenac, Celecoxib, and Flurbiprofen, [ 106 ] as well as nucleic acids like short interfering RNA (siRNA) that downregulate proinflammatory factors and protein‐degrading enzymes, but there are cases of rapid clearance by intra‐articular synovial fluid, resulting in inefficiency. [ 107 ] Nanomaterials with their scale advantage are a good carrier option to improve cargo stability and even achieve targeted therapies. [ 108 ] Conventional NP carriers can be divided into lipid‐based NPs, polymeric NPs, inorganic NPs, and a special nanocarrier derived from endogenous exosomes of animals and human body.…”
Section: Nanomedicine For Oa Therapymentioning
confidence: 99%